2015
DOI: 10.1177/1540796915602479
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coaching on a Faith Community Volunteer’s Use of Effective Teaching Behaviors

Abstract: An important part of quality of life for people with moderate and severe disabilities (MSDs) is being involved in extracurricular and community activities. However, volunteers, who may not have experience with including people with MSDs, lead most community activities. The purpose of this study was to demonstrate the effectiveness of teacher coaching on a volunteer church school teacher's use of effective teaching behaviors (opportunities to respond, behavior-specific praise, and opportunities to participate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Speraw (2006) small qualitative study of parents/caregivers of children with special needs (some of whom had ASD) found disappointing experiences with religious education, leading to crises of faith. Other studies that include some parents of children with autism spectrum disorder highlight congregational lack of support for children's participation in religious education (Ault et al 2013a;Baggerman et al 2015;Jacober 2010). Conversely, a few case studies highlight more positive and satisfactory experiences with religious education for individuals with ASD by analyzing successful adaptive and inclusion models, for example, for Bar Mitzvahs (Goldstein and Ault 2015) or Sunday School (Howell and Pierson 2010).…”
Section: Including Children With Asd In Religious Organizations: Chalmentioning
confidence: 99%
See 1 more Smart Citation
“…Speraw (2006) small qualitative study of parents/caregivers of children with special needs (some of whom had ASD) found disappointing experiences with religious education, leading to crises of faith. Other studies that include some parents of children with autism spectrum disorder highlight congregational lack of support for children's participation in religious education (Ault et al 2013a;Baggerman et al 2015;Jacober 2010). Conversely, a few case studies highlight more positive and satisfactory experiences with religious education for individuals with ASD by analyzing successful adaptive and inclusion models, for example, for Bar Mitzvahs (Goldstein and Ault 2015) or Sunday School (Howell and Pierson 2010).…”
Section: Including Children With Asd In Religious Organizations: Chalmentioning
confidence: 99%
“…At the same time, parents recognize that religious educators are volunteers with busy lives of their own, such that adding training for working with children with ASD might be difficult. However, Baggerman et al (2015) report that volunteer religious educators could successfully be coached on how to work effectively with children with moderate to severe disabilities in an inclusive religious education class. Parents also request that congregations make aides available to better help their children to participate in religious education classes.…”
Section: Recommendations For Congregationsmentioning
confidence: 99%
“…The topic of most of the articles reviewed was inclusion of people with disabilities in faith communities (n = 17, 77%). Within that category, integration in religious education classes was discussed in seven articles (Baggerman, Ault, Collins, Spriggs, & Slocum, 2015;Carmeli & Carmeli, 2008;Collins et al, 2001;Holder-Franz, 2008;Howell & Pierson, 2010;Kleinert et al, 2007;Shogren & Rye, 2005) and integration in faith community services in general was discussed in six articles (Dennis & Murdoch, 2001;Goldstein & Ault, 2015;McNair & Sanchez, 2008;Minton & Dodder, 2003;Schurter, 2006;Vogel et al, 2006). The difference between physical presence in a faith community and meaningful inclusion was discussed in three articles (Bunch, 2001;Collins & Ault, 2010;LaRocque & Eigenbrood, 2005).…”
Section: Topicmentioning
confidence: 99%
“…Carmeli and Carmeli (2008) used research methodology to investigate the effect of using symbols to teach children with ID about Jewish holidays. Baggerman et al (2015) conducted a study on teaching inclusive teacher strategies to a religious education teacher. Goldstein and Ault (2015) described a framework for building inclusive practices in a synagogue to include a child with ASD and his family.…”
Section: Type Of Articlementioning
confidence: 99%
“…Aguilar asserts that virtual coaches demonstrate a professional disposition that includes positive praise and constructive feedback that builds the teachers' pedagogical understanding. It is recommended that coaches possess content expertise and incorporate modeling of proper implementation of the skills being coached (Baggerman, Ault, Collins, Spriggs, & Slocum, 2015;Rock et al, 2012;Stormont & Reinke, 2012). Virtual coaches would have the ability to offer feedback loops in an immediate or agreed-upon delayed form to teachers being coached, if these coaches are well versed in technology (Rock et al, 2012;Scheeler, Ruhl, & McAfee, 2004).…”
Section: Virtual Coachingmentioning
confidence: 99%